pengembangan media KAMIDO berbasis metode Make a Match untuk meningkatkan penguasaan mufradat siswa kelas 8 di MTsN 4 Banda Aceh - Nurul Izzah; Mukhlisah; Rika Putri Rambe; Muhammad Akhyar (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2026)
This study aims to develop and examine the effectiveness of the Doraemon’s MagicPocket (KAMIDO) learning media using the Make a Match method to enhanceArabic vocabulary mastery among seventh-grade students at MTsN 4 Banda Aceh.This research employed the Research and Development (R&D) approach usingthe ADDIE model, which consists of five stages: Analysis, Design, Development,Implementation, and Evaluation. The research subjects were 30 seventh-gradestudents. The instruments used included interviews, observations, tests, anddocumentation. Media validation was conducted by material and media experts,yielding results of 96% and 92%, respectively, which fall under the “highly feasible”category. The effectiveness test used the One Group Pretest-Posttest Design. Dataanalysis revealed a significant improvement between the pretest score (45.50) andposttest score (88.00). The Paired Sample t-test result showed a significance value(Sig. 2-tailed) of 0.000 < 0.05, indicating a significant difference. The N-GainScore value of 0.78 or 78.69% falls into the “effective” category. Based on thesefindings, the KAMIDO learning media combined with the Make a Match methodproved to be effective, engaging, and suitable for teaching Arabic vocabulary,particularly in educational environments with limited technological resources